Study of cell apoptosis during cancer metastasis in zebrafish model. - Ngan Weida. (2013)
Resistance to apoptosis is one of the super powers for malignant cancer cells to survive through the complicated metastatic process. In our recent study, we found that high malignant cancer cells have resistance to apoptotic stimuli from the blood circulation. From these results, we hypothesize that blood circulation is a very important obstacle for cancer metastasis and thus it’s should be a best window for testing of anti-metastasis treatment. In this project, caspase-3 FRET sensor is used for detecting tumor cell apoptosis in the circulation of zebrafish embryo. The B16F10-C3 cells displayed strong resistance to apoptosis even in the presence of PI3K inhibitor, LY294002. The pre-treatment of LY294002 appeared to have down regulated adhesion integrins of the tumor cells resulting in the cell to cell adhesion to be weakened resulting in a higher percentage of cells to be arrested in the intersegmental vessel.